Phylogenetic Relationships Within Arctornis (Lepidoptera: Erebidae) Based on COI Gene Sequences - HARI SUTRISNO (Bogor Agricultural University, Indonesia, 2015)
Genus Arctornis is one of Tussock moths which are most diverse in tropics, particularly in Sundaland.Several species associate with cultivated plants and have potential to become pests. The systematic of this genus is still in dispute, especially on the monophyly and the relationship within this genus due to the fact that it is very large genus (137 described species). To clarify the monophyly of the genus Arctornis, and to reveal the phylogenetic relationship among the Indonesian species, we analyzed ten species of Indonesian Arctonis involving seven other species distributed around the world based on a 600 bp region in the COI gene. The results showed that the monophyly of Arctornis was supported by a high bayesian partition test at Maximum likelihood tree building method. The relationship among groups was supported by moderate to high bayesian partition values. Indeed, COI gene was very useful to characterize Arctornis species, especially to distinguish member of Indonesian species. Nevertheless, this should be taken with precaution because more species and more conserved genes should be involved in the future analysis to test the validity of the proposed phylogeny.